Impact of Behavioral Biases on Investment Decisions among Millennial Investors in Pokhara - Poudel, Utpal; Poudel, Resam Lal (Janapriya Journal of Interdisciplinary Studies, 2024)
The study aims to examine the impact of behavioral biases, including overconfidence bias, anchoring bias, disposition effect, and herding behavior, on investment decision-making among Nepalese investors, with a specific focus on millennial investors. A purposive sampling method was used to collect primary data, with 200 active millennial investors in Pokhara participating in the study. The research employed descriptive statistics, correlation analysis, and regression analysis to analyze the data. The findings indicate that overconfidence bias was the most prominent factor influencing investment decisions, with a significant positive impact on investor behavior. Anchoring and disposition effects also showed notable positive impacts. However, herding behavior demonstrated no significant impact on investment decisions, suggesting that Nepalese investors, particularly millennials, tend to exhibit independent decision-making behaviors rather than blindly following market trends. This study provides valuable insights for policymakers, financial institutions, and stakeholders aiming to improve investment strategies and financial decision-making in Nepal. It emphasizes the importance of understanding and managing behavioral biases, especially in the context of an emerging market like Nepal.